Hyperacute gastric perforation: A rare presentation in the post-operative period (Indian Journal of Case Reports, 2019)
Stress-related gastric ulceration and their perforation have become history because of the research and development of highly effective anti-ulcer drug and their affordability and availability across our country. We present an interesting and thought-provoking case of a 46-year-old female, with stress-related gastric perforation who developed the complication in a span of only 2 days of physiological insult.